Estres hidrico en Pinus englemannii Carr., producido en vivero - Prieto Ruiz, J.A.=700 1 Cornejo Oviedo, E.H.; Dominguez Callero, P.A.; Navar Chaidez, J. de J.; Marmolejo Moncivais, J.G.; Jimenez Perez, J.
(En, Es)
ilus., 40 ref.
Keywords: PINUS; DEFICIT DE HUMEDAD; CALIDAD; PLANTA; CRECIMIENTO; ESPAÑA; PINUS ENGLEMANNII; ESTRES HIDRICO